Is All Seagrass Habitat Equal? Seasonal, Spatial, and Interspecific Variation in Productivity Dynamics Within Mediterranean Seagrass Habitat - Ward, Emma A.; Aldis, Charlotte; Wade, Tom; Miliou, Anastasia; Tsimpidis, Thodoris; Cameron, Tom C. (Frontiers in Marine Science, 2022)
Seagrass meadows’ ability to capture carbon through sequestering autochthonous carbon via photosynthesis means they could represent a potential nature-based solution to rising carbon emissions. In multispecies seagrass communities, and due to species introduction or predicted range shifts, it is important to know which species deliver different carbon sequestration gains to inform conservation actions. Large benthic chamber experiments (volume = 262L) assessed the seasonal and spatial variation in metabolism dynamics of the endemic and dominant Mediterranean seagrass, P. oceanica whilst small benthic chamber experiments (volume = 7L) compared the dynamics between, P. oceanica the native C. nodosa and non-native H. stipulacea. Within shallow P. oceanica edge habitat lower Net Apparent Productivity (NAP) occurs in autumn (x¯ = 1.3, SD ± 2.95 O2 mmol m-2 d-1) compared to summer (x¯ = 9.9, SD ± 2.75 O2 mmol m-2 d-1 corresponding with periods of light limiting and light saturating conditions, but it remains overall autotrophic annually (2.3 C mol m-2 yr-1). However, spatial heterogeneity exists, the center areas of P. oceanica were more productive (NAP x¯ =19.7, SD± 3.83 O2 mmol m-2 d-1) compared to edge habitat with spatial changes in productivity relating to plant surface area (96%), shoot density (81%), blade length (72%) and seagrass percentage cover (64%). Under comparative conditions in a sparse multispecies area of the meadow the species demonstrated different capacities for carbon fixation. H. stipulacea was carbon positive and P. oceanica fluctuated between positive and negative carbon balance suggesting both can maintain a balance between carbon fixation and carbon utilised for metabolic activity. In contrast the C. nodosa here would be expected to deteriorate as it was utilising carbon more than it was fixing (NAPN2 (x¯ = -0.0012, SD ± 0.0007 O2 mmol cm-2 d-1). This study demonstrates that not all seagrass habitat is equal. If seagrass meadows are to play a part in mitigating CO2 emissions, variability in primary productivity within seagrass meadows needs to be accounted for to produce accurate total fixed carbon estimates, and subsequently autochthonous carbon sequestration estimates. This means seagrass meadow species composition and the condition of these meadows must be better understood.